2019
DOI: 10.1083/jcb.201907178
|View full text |Cite
|
Sign up to set email alerts
|

Hair follicle regeneration suppresses Ras-driven oncogenic growth

Abstract: Mutations associated with tumor development in certain tissues can be nontumorigenic in others, yet the mechanisms underlying these different outcomes remains poorly understood. To address this, we targeted an activating Hras mutation to hair follicle stem cells and discovered that Hras mutant cells outcompete wild-type neighbors yet are integrated into clinically normal skin hair follicles. In contrast, targeting the Hras mutation to the upper noncycling region of the skin epithelium leads to benign outgrowth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 51 publications
(70 reference statements)
4
38
0
Order By: Relevance
“…Pineda et al additionally induced Hras G12V expression in the skin epithelium (6). Hras mutant cells in the skin epidermis showed hyperproliferation and outcompeted their WT neighbors, like Hras G12Vexpressing HF cells.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Pineda et al additionally induced Hras G12V expression in the skin epithelium (6). Hras mutant cells in the skin epidermis showed hyperproliferation and outcompeted their WT neighbors, like Hras G12Vexpressing HF cells.…”
mentioning
confidence: 99%
“…Pineda et al induced Hras G12V expression in Krt19 + HFSCs during the first HF regression and followed the cells over time (6). Surprisingly, the authors observed that although mutant cells proliferated more frequently than WT neighbors, they generally followed the cues of HF regeneration and regression over multiple hair cycles ( Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations